The Behavioral Implications of a Multi-Individual Bonebed of a Small Theropod Dinosaur - Ibiricu, Lucio M. (2013)
Fil: Ibiricu, Lucio M. Consejo Nacional de Invest.cientif.y Tecnicas. Centro Nacional Patagonico; Argentina